1996
DOI: 10.1126/science.271.5254.1395
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Catalytic Behavior of Zeolites: A First-Principles Study of the Adsorption of Methanol

Abstract: Zeolites are microporous aluminosilicate materials used as industrial catalysts, and there is much interest in understanding their catalytic behavior. The adsorption of methanol in the catalytically active zeolite chabazite and in sodalite was examined by performing ab initio calculations within periodic boundary conditions. A direct correlation between zeolite structure and chemical activation of the adsorbate was found. Methanol was protonated without an activation energy by a Brønsted acid site, provided th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 12 publications
5
109
2
Order By: Relevance
“…The plane-wave cutoff chosen was 55 Ry. This is very close to planewave cutoffs used by other researchers [13,14], and we have found that it yields the gas-phase proton affinity of methanol to be 183.7 kcal mol À1 , compared to 185.1 kcal mol À1 experimentally [15]. Only the À point was sampled in the Brillouin zone.…”
Section: Methodssupporting
confidence: 77%
“…The plane-wave cutoff chosen was 55 Ry. This is very close to planewave cutoffs used by other researchers [13,14], and we have found that it yields the gas-phase proton affinity of methanol to be 183.7 kcal mol À1 , compared to 185.1 kcal mol À1 experimentally [15]. Only the À point was sampled in the Brillouin zone.…”
Section: Methodssupporting
confidence: 77%
“…Although full periodic calculations are now feasible using methods evolved from the area of molec-Ž . 28 ular ab initio structure calculations CRYSTAL and from plane-waverdensity functional methods of solid state physics, 13,33 methods that are more computationally economic are certainly needed. It is clear that quite simple schemes, employing an electrostatic correction to bare cluster models, are very effective.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the alcohol, the acidity and topology of the zeolite framework and the coverages of the guest molecules determine the final outcome [70,71,72]. Also for the CHA topology, a broad set of theoretical calculations were performed but they initially did not uniquely determine the answer as the final outcome is largely dependent on the particular theoretical protocol that was used for the calculations (periodic versus cluster calculations, size of the cluster) [70,71,72,73,74,75,76]. Small cluster calculations lead to the observation that methanol was physisorbed on the acid site, whereas Shah et al used periodic DFT calculations to reveal that the optimized geometry of adsorbed methanol in CHA corresponds to the methoxonium ion (i.e.…”
Section: Physisorption Of Methanol and Ethanol In H-sapo-34 From Firsmentioning
confidence: 99%